2017
DOI: 10.2147/jaa.s147005
|View full text |Cite
|
Sign up to set email alerts
|

Study of the clinical and functional characteristics of asthmatic children with obstructive sleep apnea

Abstract: Background and objectiveThe obstructive sleep apnea (OSA) is a common respiratory disorder in children, especially those at preschool and school ages. This study aimed to describe the characteristics of asthmatic children with OSA and the symptoms for a high risk of OSA.Subjects and methodsIt was a prospective and descriptive study. The data of asthmatic children including medical history, clinical examination, blood tests, spirometry, exhaled nitric oxide (NO), and respiratory polygraphy were registered for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
3
14
1
Order By: Relevance
“… 44 Over the last 15 years, about one-third of the studies failed to show the presence of a significant association between rhinitis and overall sleep disorders ( Table 1 ). 35 , 38 , 40 , 41 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 The very low-grade level of evidence was further corroborated in a more recent systematic review and meta-analysis evaluating the association between AR and sleep, based on observational investigations in children and adults. 4 Adjusted odds ratios revealed that AR was associated with a higher risk of nocturnal dysfunction, including insomnia, nocturnal enuresis, restless sleep, SDB, OSA, snoring, daytime dysfunction, including difficulty waking up, daytime sleepiness, morning headache, and the use of sleep medications.…”
Section: Association Between Ar and Sleep Disordersmentioning
confidence: 82%
See 1 more Smart Citation
“… 44 Over the last 15 years, about one-third of the studies failed to show the presence of a significant association between rhinitis and overall sleep disorders ( Table 1 ). 35 , 38 , 40 , 41 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 The very low-grade level of evidence was further corroborated in a more recent systematic review and meta-analysis evaluating the association between AR and sleep, based on observational investigations in children and adults. 4 Adjusted odds ratios revealed that AR was associated with a higher risk of nocturnal dysfunction, including insomnia, nocturnal enuresis, restless sleep, SDB, OSA, snoring, daytime dysfunction, including difficulty waking up, daytime sleepiness, morning headache, and the use of sleep medications.…”
Section: Association Between Ar and Sleep Disordersmentioning
confidence: 82%
“… 48 8–18 287/143 Case- controlled Medical records, clinical examination and SPT Face-to-face interview Sleep quality (PSQI outcomes) 2017 Tsai JD et al . 49 5–18 8616/4191 Case- controlled Medical records, clinical examination Medical records Nocturnal enuresis 2017 Nguyen- Hoang Y et al 50 6-17 85/52 Case- controlled Clinical examination Medical records OSA in asthmatics 2016 Di Francesco RC, Alvarez J 38 3–14 135/57 Case- controlled Self-reported, Rhinoscopy and SPT PSG PSG outcomes (AHI) 2015 Poachanukoon O, Kitcharoensakkul M 51 6-15 175/65 Case- controlled Medical records, clinical examination and SPT Self-reported Sleep duration, difficult waking up, snoring, morning headache, mouth breathing, night sweating, nocturnal enuresis, OSA daytime sleepiness, restless sleep, SDB, sleep bruxism 2014 Weinstock TG et al. 41 5-9.9 464/110 Cross-sectional Physician-diagnosed PSG AHI severity 2014 Ng DK et al.…”
Section: Association Between Ar and Sleep Disordersmentioning
confidence: 99%
“…The prevalence of OSA in children with asthma ranges from 35 to 66% 89,90 ; in adults, prevalence is reported to be 40-50% 91,92 . In the general population, estimates of OSA prevalence are in the range of 3-7% 93 .…”
Section: Obstructive Sleep Apnoea Prevalencementioning
confidence: 99%
“…There is a growing body of population-based research on the association between AR and sleep patterns. AR has been found to be positively associated with sleep-disordered breathing (SDB) [20], obstructive sleep apnea (OSA) [21], shorter sleep duration [22], poor sleep quality [23], sleep bruxism [24], night sweating [25], nocturnal enuresis [26], and daytime dysfunction [27]. However, these results are also controversial, since several studies found a negative or insignificant relationship between AR and the above sleep-related outcomes [7,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%